2017
DOI: 10.23822/eurannaci.1764-1489.12
|View full text |Cite
|
Sign up to set email alerts
|

The link between chronic spontaneous urticaria and metabolic syndrome

Abstract: Summary Metabolic syndrome (MS) is a cluster of risk factors for cardiovascular disease and is considered a chronic low-level systemic inflammatory condition. Recent preliminary findings have shown an increased prevalence of MS among patients with chronic urticaria (CU) as compared to controls, with a particularly higher prevalence detected in patients with uncontrolled CU. Chronic spontaneous urticaria (CSU) appears to share some pathomechanisms with MS, including a pro-inflammatory state, increased oxidative… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 31 publications
1
11
0
3
Order By: Relevance
“…In particular, AD is associated with allergic disorders representing the ‘atopic march’, 23 whereas PSO and CU are significantly associated with psoriatic arthritis on the one hand and thyroid autoimmunity on the other 24,25 . Despite a lower rate of cardiovascular risk factors and disorders in our AD cohorts compared with PSO and CU patients, associations with cardiovascular and neuropsychiatric comorbidities, potentially related to systemic inflammation, may also affect patients with AD 26‐30 . Thus, recent insights into the systemic nature 31 of AD eclipse the misconception that AD is just a ‘skin‐deep’ condition and will probably impact the AD therapeutic management 32 …”
Section: Discussionmentioning
confidence: 90%
“…In particular, AD is associated with allergic disorders representing the ‘atopic march’, 23 whereas PSO and CU are significantly associated with psoriatic arthritis on the one hand and thyroid autoimmunity on the other 24,25 . Despite a lower rate of cardiovascular risk factors and disorders in our AD cohorts compared with PSO and CU patients, associations with cardiovascular and neuropsychiatric comorbidities, potentially related to systemic inflammation, may also affect patients with AD 26‐30 . Thus, recent insights into the systemic nature 31 of AD eclipse the misconception that AD is just a ‘skin‐deep’ condition and will probably impact the AD therapeutic management 32 …”
Section: Discussionmentioning
confidence: 90%
“…Several large studies have shown an association of CSU with hypertension and obesity (> 20%), 13,19–21 and a few also report a higher frequency of both hyperlipidaemia and metabolic syndrome 107,108 …”
Section: The Burden Of Chronic Urticaria Comorbiditiesmentioning
confidence: 99%
“…31 Several large studies have shown an association of CSU with hypertension and obesity (> 20%), 13,[19][20][21] and a few also report a higher frequency of both hyperlipidaemia and metabolic syndrome. 107,108 Given the debilitating nature of CSU, it is not surprising that >30% of patients experience psychiatric comorbidities including anxiety, depression and somatoform disorders, with a significant negative impact on their QoL. 13,20,109,110 An association between CSU and headaches has been reported, which can affect QoL, particularly in children.…”
Section: Angio-oedema Further Deteriorates Health-related Quality Of mentioning
confidence: 99%
“…Chronic low grade inflammation associated with high stress scores, raised C-reactive protein and interleukin 18 [84] may explain the increased frequency of metabolic syndrome in CSU [88, 89]. Hypertension was noted in 18.1% of the 1539 CSU patients that were analysed as part of the German contribution to the AWARE study [90].…”
Section: Aetiological and Associated Factors In Csumentioning
confidence: 99%